Mineralization crust field experiment for desert sand solidification based on enzymatic calcification. (1st June 2021) - Sun, Xiaohao; Miao, Linchang; Wang, Hengxing; Yin, Wenhua; Wu, Linyu
Abstract: Sandstorms have been recognized as severe natural disasters worldwide and it is of great significance to propose an effective and environmentally friendly method to combat sandstorm. In this study, the enzymatic calcification (EC) treatment technology was used for mineralization crust and desert sand solidification. Both laboratory experiments and field site tests were conducted to demonstrate the feasibility of EC treatment to improve wind-erosion resistance and rainfall-erosion resistance. Results showed that with the concentration of reactants higher than 0.25 M or the ratio of urease solution to the cementation solution above 0.8, the improvement effects of wind-erosion resistance and rainfall-erosion resistance decreased. Therefore, the 0.25 M of reagent concentration and 0.8 of ratio of urease solution to the cementation solution were chosen for subsequent field site test. The two test sites had similar CaCO3 contents, thus obtaining a similar increasing range of surface strength. However, the test site one had larger surface strengths due to thicker cemented crust layers. Both the two test sites had sufficient wind-erosion resistance because of crust layer. Moreover, rainfalls decreased surface strength; the surface strength recovered to a high level after water evaporation. In addition, the effect of rainfall on thickness of crust layer and CaCO3 was small. The EC treatment had good ecological compatibility, and the combined EC and grass seed treatment was effective for mitigation of desertification. The results demonstrated that EC treatment significantly improved both wind-erosion and rainfall-erosion resistance, which presents promising potential for anti-desertification. Highlights: We proposed an effective and environmentally friendly method for sandstorm control based on enzymatic calcification (EC). The wind-erosion and rainfall-erosion resistance in field sites are improved with EC and added polyvinyl acetate. The EC treatment has good ecological compatibility, which is effective for mitigation of desertification.